Upaya Pemenuhan Rasa Nyaman Pada Ibu Hamil Trimester-III Dengan Nyeri Punggung - Fauziah Fatmawati, Fitriana; , Sulastri, S.Kp., M.Kes; , Faizah Betty R., A., S.Kep ., M.Kes (2017)
Abstrack Abstract Background: There are several problems that arise in the third trimester pregnant women such as back pain. The cause of lower back pain one of which is due to hormonal changes that cause changes in the soft tissues and connective buffer so that the decrease in the elasticity and flexibility of muscles. The negative impact of lower back pain is that it can cause a negative impact on quality of life for pregnant women because of the disruption of daily physical activity. To reduce back pain pregnant women nurses can be a member of interventions such as assessing pain scale and assess the causes inconveniences clients, providing health education about pain, teach relaxation techniques breath in, teach improvements posture in pregnant women, teaches a comfortable sleeping position with a pillow supporting and positioning alternately slant bed, teaches choose clothes for pregnant women, teaches warm compresses on the pain. Objective: provide measures in order to improve comfort to the third trimester III pregnant women associated with back pain. Methods: The descriptive method with case study approach is a scientific method that is collecting the data, analyze the data and draw conclusions data. Result: after the act of nursing for 3-day visit is expected to house patients can improve compliance with a sense of comfort associated with back pain. Conclusion: Nursing problem that accur in patients can be overcome in part so that intervensionsneed to be in advanced.